Rare and atypical presentations of endometriosis causing diagnostic dilemma and management challenges: an experience at a tertiary center - Dalal, Vinod K.; Magdum, Hrishikesh; Tangri, Manoj K.; Malhotra, Gunjan; Ashisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Endometriosis is a disease that most of the times is diagnosed by its common presenting sign and symptoms, but can have varied presentations and may come as a surprise during surgery. We here present a case series of unusual presentations of endometriosis, which created diagnostic dilemma and challenges in the management of the cases at this tertiary center and share our experience. Endometriosis must be kept as a differential diagnosis whenever patient presents with acute pelvic or abdominal pain with adnexal masses and things are not fitting into straight forward diagnosis.